E-training Environment for Developing Capstone Teaching Skills for STEM Teachers in Egypt - Noha Anbar; Tarek Hegazy; Mohamed El Naggar (European Scientific Journal, ESJ, 2024)
The research investigated the effectiveness of using an E-training environment in developing Capstone teaching skills among STEM teachers. To achieve the aim of the research, the researchers applied the one groups' quasi-experimental design and utilized three instruments as follows;1) list of the Capstone teaching skills; 2) Pre-Post achievement test developed by the researcher and implemented before and after applying the training content; 3) The observation card to observe acquiring the Capstone teaching skills  determined by the researcher and they are two main fields of the needed skills, (EDP Field, and Process management field) comprising eight (8) main skills that are subdivided into sixty four (64) subskills required for the STEM teachers, after applying the training content through the E-training environment. The participants were chosen randomly (N=27) at Obour STEM School Cairo Governorate, Egypt. the researchers selected the quasi-experimental design in terms of the research population, the sample of the research, is one experimental group, and the methodology of the research. The researchers relied on pre-and post-testing procedures applied on the research group, the first test has been posted to the trainees after collecting their responses on the training needs survey or a questionnaire that included 68 questions to identify their needs, the pre-test comprises 70 questions about the 64 sub-skill, then after that the training needs have been determined based on the pre-test results, through a month the training has been held Online on the Microsoft Teams as a main platform, by the end of the training sessions, the trainees have been asked to solve the post-test which is reapplied once again after another month .Therefore, the current research attempted to investigate the effectiveness of using the E-Training environment based on the SOLE technique as (the independent variable) in developing the Capstone teaching  skills as (the dependent variable) among STEM teachers. Quantitative results showed that There is statistically significant difference at the level of (a<=0.05) between the pre-test and post- achievement test of the experimental group on developing Capstone teaching achievement of STEM teachers in favor of the post -test. And also, there is statistically significant difference at the level of (a<=0.05) between the pre-test and post- observation card of the experimental group on developing Capstone teaching skills of STEM teachers in favor of the post -test.So, the researchers recommended employing the E-Training environment based on the SOLE technique in developing the Capstone teaching skills among STEM teachers in Egypt.